Emotional Stability and Self-Efficacy in Achieving Career Success - Noerchoidah, Noerchoidah; Indriyani, Ratih; Wahyuni, Dewi Urip; Arianto, Bisma (Universitas Islam Lamongan, 2023)
This study intends to provide practical and theoretical insights into how employees maintain emotional stability and self-efficacy in achieving career success in hospitality employees in Surabaya. This study used a quantitative method using a questionnaire given to 123 respondents. This research used a purposive sampling technique. This study uses Partial Least Square (PLS) software in analyzing data. The results of the study found that emotional stability has a positive and significant effect on employee self-efficacy. Self-efficacy has a significant positive effect on employee career success. Emotional stability has a significant positive effect on employee career success. Self-efficacy has a positive and significant effect in mediating the emotional stability and career success of hotel employees in Surabaya. The results of this study support the social cognitive theory.